Encyclopedia of practical horticulture fruits - Sharma, V K (New Delhi Deep and Deep, 1999)
The present book Encyclopaedia of practical Horticulture a set of 4 volumes covers the latest technical how regarding the production,protection and presentation of Fruits vegitables,ornamental plants and ornamental Trees, in a simple language so that our
Contents:v.1. Fruits -v.2. Vegetables -v.3. Ornamental Plants -v.4. Ornamental Trees
Keywords: Horticulture-Encyclopedias; Fruits; Horticultural crops; Vegetables; Plants, Ornamental; Ornamental Horticulture; Ornamental trees